On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

A process for the preparation of a population inversion in a quantum system using multi-pulse excitation - Zrenner, Artur; Förstner, Jens; Mantei, Dirk
Die Erfindung betrifft ein Verfahren zur Präparation einer Besetzungsinversion in einem Quantensystem (Q) mittels Mehrpulsanregung, wobei ein Quantensystem (Q) umfassend wenigstens einen Quantenpunkt mit zwei orthogonalen Zuständen (/X>, /Y>), insbesondere die mit zueinander orthogonalen Polarisationen (P1, P2) optisch anregbar sind, mit einem ersten Laserpuls (L1) beleuchtet wird, welcher zur resonanten Anregung des ersten (/Y>) der zwei Zustände (/X>, /Y>) eingestellt wird und zeitlich nachfolgend mit einem zweiten Laserpuls (L2) beleuchtet wird, der zur resonanten Anregung des zweiten (/X>) der zwei Zustände (/X>, /Y>) eingestellt wird.
Keywords: tet_topic_qd

Cubic GaN quantum dots embedded in zinc-blende AlN microdisks - Bürger, M.; Kemper, R.M.; Bader, C.A.; Ruth, M.; Declair, S.; Meier, Cedrik; Förstner, Jens; As, D.J. (Journal of Crystal Growth)
Microresonators containing quantum dots find application in devices like single photon emitters for quantum information technology as well as low threshold laser devices. We demonstrate the fabrication of 60 nm thin zinc-blende AlN microdisks including cubic GaN quantum dots using dry chemical etching techniques. Scanning electron microscopy analysis reveals the morphology with smooth surfaces of the microdisks. Micro-photoluminescence measurements exhibit optically active quantum dots. Furthermore this is the first report of resonator modes in the emission spectrum of a cubic AlN microdisk.
Keywords: tet_topic_qd; tet_topic_microdisk